Mutation Frequency in Mungo ( Phaseolus radiatus L.) After Treatment with an Alkylating Chemcial Mutagen - Palima, Corbelita; Soriano, Joventino (Science Diliman: A Journal of Pure and Applied Sciences; Vol 1 (1980), 2007)
Dormant seeds of green mungo ( Phaseolus radiatus L.) were treated with aqueous solution of EMS at concentrations of 0.02M to 0.06M with phosphate buffer for periods of 6 to 24 hours at approximately 30°C. Seeds soaked in distilled water and buffer solution were used as controls. The seeds were grown on moist blotting paper for germination percentage and seedling height measurements after seven days. The M 1 seedlings were transplanted in field plots in a dose-to-row plan with two replications for determination of the frequency of somatic mutations, percentage of field survival at flowering stage, and seed-set. The M 2 progenies were grown for determination of types and frequency of chlorophyll-deficient mutations as an index of the degree of genetic change due to the mutagen. In general, a direct dose-effect relationship was obtained for the various biological criteria employed to measure the effectivity of the mutagen. These are percentage of germination after treatment, seedling height, somatic mutations, seed-set and germinal mutations. Three types of induced chimeral sectors on leaves of M 1 plants such as pale green, yellow green and yellow occurred with a frequency ranging from 4.65 to 31.03 per cent. Four types of chlorophyll-deficient seedling mutations were obtained, i.e., virescent, chlorina, xantha and albina with a frequency ranging from 0.23 to 7.55 per cent on the seedling basis and 2 to 26 per cent on the pod basis.